Water availability, use and challenges in Pakistan: Water sector challenges in the Indus Basin and impact of climate change - Wahaj, Robina; Habib, Zaigham; Rana, Abdul Wajid (Food and Agricultural Organization of the United Nations, 2021)
This working paper takes stock of Pakistan's water resource availability, delineating water supply system and its sources including precipitation and river flows, and the impact of increasing climatic variability on the water supply system. In particular, the paper focuses on the current water usage and requirements in the agricultural sector, and how changing climatic conditions will affect the consumption patterns. With inflows expected to become more variable in the coming years, the severity of climatic extremities will become more pronounced, driving up water demands in addition to the demand increase from a rising population and urbanization. Over extraction of groundwater resources is also disturbing the water calculus and pushing the country towards a critical demand-supply gap.